Dry matter, starch content, reducing sugar, color and crispiness are key parameters of potatoes required for chip processing - Islam, Md Mazadul; Naznin, Sauda; Naznin, Afroz; Uddin, Md Nasir; Amin, Md. Nurul; Rahman, Md. Mushfiqur; Tipu, Mohammad Monirul Hasan; Alsuhaibani, Amnah Mohammed; Gaber, Ahmed; Ahmed, Sharif (MDPI, 2022)
To make potato production more sustainable for smallholder farmers, product diversification through processing is critical. On the other hand, the processing sector mandated some stringent standards in order to maintain product quality, hence potato quality evaluations are required for chip processing industries. Specific gravity, starch, reducing sugars, tuber dry matter, and chip color are all important characteristics to consider for processing. This study was designed to find suitable potato varieties with satisfactory attributes for processing chips, in comparison with other processing potato varieties. Keeping this in mind, the study was performed during the winter season of 2019–2020 and 2020–2021 in Bangladesh. Six processing types of potato varieties viz. BARI Alu-25 (Asterix), BARI Alu-28 (Lady Rosetta), BARI Alu-29 (Courage), BARI Alu-68 (Atlantic), BARI Alu-70 (Destiny), and BARI Alu-71 (Dolly) were evaluated for different quality parameters (specific gravity, dry matter, starch content, reducing sugar, chip color, and crispiness). The result of the study showed an ample variation in the studied parameters among the potato varieties. Among the varieties, BARI Alu-28 (Lady Rosetta) and BARI Alu-29 (Courage) were found better for all the quality parameters, such as dry matter, starch, reducing sugar, chip color, and crispiness, and could be recommended for the processing industries.